Tren konsumerisme remaja di era digital pada pengaruh iklan, influencer, dan budaya digital - Ulum, Ilsa Fikrotul (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze trends in youth consumerism in the digital age, focusing on the influence of advertising, the role of influencers, and digital culture. The method used is a literature review through searching various scientific journals, research articles, and relevant bibliographic sources. The results of the study show that social media plays an important role in shaping adolescent consumptive behavior through algorithm-based promotion systems, continuous exposure to digital advertising content, and personalized product recommendations. Influencers and celebrity Instagrammers have become figures in their lifestyle, so that adolescents tend to imitate the consumption patterns of their idols due to parasocial relationships. The findings of the theoretical study reinforce that consumptive behavior is not only influenced by practical needs, but also by status symbols, social identity, and comparisons with the digital environment. Symbolic consumption theory, social comparison theory, and the perspective of digital capitalism explain that digital media creates artificial needs, impulsive buying urges, and social pressure to always follow trends. This study emphasizes the importance of digital literacy, advertising and promotion regulations, and character education as strategic steps to minimize the negative impact of consumerism on adolescents.